Gambaran Infeksi Soil Transmitted Helminth Pada Petani Di Desa Gelgel Kabupaten Klungkung - putu indah budi apsari; Ni Wayan Winianti; Heny Arwati; Yoes Prijatna Dachlan (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2020)
Soil transmitted helminth (STH) infections is kind of helminth infection which transmitted by contact with warm and moist soil especially affect the farmer. The purpose of this study was to investigate the profile of STH infection and the intensity of STH infection among farmers in Gelgel Village, Klungkung, Bali. The cross sectional study was conducted in Gelgel Village, Klungkung District, Bali and obtained stool and quitionaires from farmers by informed consent. Kato-Katz technique was used to diagnose the STH infection and to determine the intensity of infection based on the number of eggs per gram feces (EPG). Total 162 stool samples were collected from farmers aged 25-80 years, 22 farmers was positive of STH infection and 140 farmers was negative of STH infection. The result showed prevalence of STH infection was 13,5%, single infection of A. lumbricoides was 1.85%, 9.26% of T. trichiura single infection, and 0.61% of Hookworm single infection. The mixed infection was detected that were 1.23% of A. lumbricoides with T. trichiura, and 0.61% of A. lumbricoides with Hookworm. STH infection is the health problem among farmer. The farmer must be admitted antihelminthic drugs for preventing and eleminating STH infection.